The impact of fisheries and maritime transport export on economic growth: The case of Türkiye - Erdal Arlı; Mehmet Sıtkı Saygılı; İlkay Sultan Güneş (Transportation Research Interdisciplinary Perspectives)
Several key sectors play a critical role in supporting both global and national economic development. For coastal countries such as Türkiye, the fisheries and maritime freight transport sectors are particularly significant drivers of economic growth, primarily through their export-oriented activities. This study analyses the effect of Türkiye’s fisheries and maritime freight exports on economic growth over the period 2000–2019, using various econometric techniques. These include cointegration tests, Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), Canonical Cointegration Regression (CCR), Granger causality tests, and variance decomposition analysis. The findings show that in the short term, combined exports from fisheries and maritime freight sectors Granger-cause economic growth at the 0,01 level of significance. In the long term, both types of exports positively affect economic growth. By the sixth year, their contributions become almost equal, indicating a long-run equilibrium and co-movement. By the nineteenth year, fisheries exports explain 19.7% of the changes in economic growth, while maritime freight exports account for 18.3%, highlighting the strategic role of both sectors in Türkiye’s economic performance.